Sequence variation of bovine mitochondrial ND-5 between haplotypes of composite and Hereford Breeds of beef cattle - SUTARNO SUTARNO (Society for Indonesian Biodiversity, 2002)
The aims of the study were to: Investigate polymorphisms in the ND-5 region of bovine mitochondrial DNA in the composite and purebred Hereford herds from the Wokalup selection experiment, sequencing and compare the sequences between haplotypes and published sequence from Genebank. A total of 194 Hereford and 235 composite breed cattle from Wokalup Research Station were used in this study. The mitochondrial DNA was extracted using Wizard genomic DNA purification system from Promega. ND-5 fragment of mitochondrial DNA was amplified using PCR and continued with RFLP. Each haplotypes were sequenced. PCR products of each haplotype were cloned into pCR II, transformed, colonies selection, plasmid DNA extraction continued with cycle sequencing. Polymorphisms were found in both breeds of cattle in ND-5 region of mitochondrial DNA by PCR-RFLP analysis. Sequencing analysisconfirmed the RFLPs data.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey words: ND-5 mitochondrial DNA, PCR-RFLP, sequencing, polymorphism.